Integrating Resilience and Sustainability into Civil Engineering Projects - Field, Caroline; Zawislak, Chris; Harper, Ben; Davidson, Cliff Ian; Eide, Fran; Rosenberg, Heather; Hegelson, Jennifer; McNeil, Sue (Infrastructure resilience publication., 2023)
Integrating Resilience and Sustainability into Civil Engineering Projects, Infrastructure Resilience Publication 6, describes how the engineering community is working to integrate social science, policy, and economics into the planning, design, and management decisions surrounding physical infrastructure projects.